The Integration of Primary Care and Public Health in Medical Students’ Training Based on Social Accountability and Community-Engaged Medical Education - Jaime Kristoffer Punzalan; Monserrat Guingona; Mary Germeyn Punzalan; Fortunato Cristobal; Annika Frahsa; Harvy Joy Liwanag (International Journal of Public Health, 2023)
Objectives: Primary care and public health comprise the bedrock of health systems, but their divergence has produced two groups of practitioners either focused on individual health or population health. We explored how primary care and public health were integrated in medical students’ training in Zamboanga Peninsula, Philippines.Methods: Our qualitative study reviewed community health plans in two municipalities and thematically analyzed the perspectives of medical students, faculty, alumni, and community stakeholders through focus group discussions and in-depth interviews.Results: Integration began by operationalizing a curriculum requiring medical students to serve rural communities during most of their training—a departure from the conventional, hospital-based medical education in the Philippines. The medical students’ community immersion provided opportunities for integrating primary care and public health activities that influenced their personal orientations and the health situation in communities. Integration continued after training as alumni found themselves serving as primary care and public health practitioners in the region.Conclusion: Social accountability and community-engaged medical education provided the foundation for medical students to integrate primary care and public health in practice to respond to local needs.